(untitled) (Progressive Agriculture, 2014)
An experiment was conducted at the Hill Agricultural Research Station, Khagrachari from May to November 2004 to find out the effect of planting time (1st week of June, July, August and September) and plant spacing (60 × 30 cm, 60 × 40 cm and 60 × 50 cm) on the yield and yield components of okra in hill slope condition during rainy season. The highest yield (12.53 t/ha) was obtained by the planting in July which was at par with June (11.69 t/ha). In case of plant spacing, the highest yield (9.02 t/ha) was recorded from close spacing at 60 x 30 cm that was statistically different from other two spacing and the widest spacing of 60 x 50 cm produced the lowest yield (8.06 t/ha). The treatment combination July sowing with 60 x 30 cm plant spacing produced significantly highest yield (12.86 t/ha). DOI: http://dx.doi.org/10.3329/pa.v18i2.18161 Progress. Agric. 18(2): 67 - 73, 2007